(untitled) (Neo Scientific Peer Reviewed Journal, 2025)
This scientific article explores the intricate dynamics of scene action, shedding light on the interplay between purpose and given situations. Scenes, as contextual settings, provide a stage where actions unfold, driven by specific goals and intentions. The understanding of scene action is crucial in various fields, including psychology, sociology, and artificial intelligence, as it contributes to unraveling the complexities of human behavior and decision-making.